PENGARUH HARGA DAN PROMOSI GRAB TERHADAP BRAND IMAGE YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN PENGGUNA TRANSPORTASI BERBASIS ONLINE - Leksono, Rafael Billy; Herwin, Herwin (Economic Faculty, Attahiriyah Islamic University, 2017)
This research aims to understand the influence of the price set and promotional activities of Grab towards consumer purchase decision of through brand image as intervening variables. This research is a quantitative research. A number of samples taken are 205 people using people purposive sampling technique. the measurement used was the questionnaire that was disseminated through Google Form and analysis using SPSS 20. The results of hypothesis analysis show that price influence significantly to brand image; promotion influence significantly to brand image; price influence significantly to purchase decision; promotion influence significantly to purchase decision, and brand image influence significantly to purchase decision. Keywords: price, promotion, consumer purchase decision, brand image